Complex Treatment of Chronic Adenoiditis Using Phototherapy - Ikramova F.S.; Alimova Sh.A. (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
In the period from 2021 to 2022, we examined 70 children who applied to the Bukhara Regional Children's Multidisciplinary Medical Center ENT department. The age distribution was as follows: children of the first year (7 months to 11 months) – 2 (3%), early age (from 1 to 2 years) – 16 (22.8%), preschool (3 l – 6 years) - 33 (47.2%) and school age (7 l – 11 years old) – 19 (27.3%) children. Patients of preschool age (from 3 to 6 years, 47.2%) prevailed among the patients. The use of photodynamic therapy in the complex therapy of chronic adenoiditis eliminates tubar dysfunction and snoring 5 times faster and normalizes nasal breathing 3 times faster than with traditional treatment, improving the indicators of anterior active rhinomanometry in total volume flow 4 times, and in total resistance 20 times, which indicates adequate inclusion of hypertrophied pharyngeal tonsil to the zone of therapeutic effect of the new method.